WasserWesenWandel: Fluidität in (mehr-als-)literarischen Medien. Sammelband zur fünften studentischen Tagung des Fachbereichs Komparatistik an der Universität Paderborn

Die Grammatik des gesprochenen und geschriebenen Französisch als erste korpusbasierte Lexikogrammatik des Französischen: Grundlagen, Prinzipien, Umsetzung - Bürgel, Christoph; Siepmann, Dirk (Fremdsprachen Lehren und Lernen (FLuL), 33-48)

Modelling Deformation Mechanisms Decomposition, Separation and Compaction in Mechanical Joining Processes of Fiber Reinforced Thermoplastics on Meso Scale - Gröger, Benjamin; Gerritzen, Johannes; Hornig, Andreas; Gude, Maik (Key Engineering Materials)
The mechanical joining of continuous fiber-reinforced thermoplastics (cFRTP) and metal sheets represents a promising approach for manufacturing hybrid lightweight structures. To reduce the time and cost associated with extensive experimental investigations, numerical modeling strategies are increasingly applied. In this numerical study, a further step in the modelling strategy for the direct pin-pressing (DPP) process of cFRTP and metal sheets is presented. The study focuses on modeling and simulating the occurring deformation mechanisms of decomposition, compaction, and separation of individual rovings on the mesoscale to analyze the resulting material structure. For this purpose, two simplified models were derived. The textile architecture is represented based on micrographs of cross-sections and discretized using the finite element method. The deformation of individual rovings during joining leads to a deformation of their initial elliptical cross section. To capture this level of resolution, both a cohesive zone and a pure contact approach are applied within the rovings. The highly viscous thermoplastic melt is modeled as a fluid employing the Arbitrary Lagrange–Eulerian (ALE) method. Matrix and roving meshes are coupled to account for fluid–structure interaction (FSI) during process. The study shows that coupling of matrix and rovings is necessary to obtain more accurate predictions of the deformation behaviour. Furthermore, the cohesive zone approach is better suited to simulate the emerging deformation mechanisms.

Discounted Sales of Expiring Perishables: Challenges for Demand Forecasting in Grocery Retail Practice - Winkelmann, David; Elbracht, Theresa; Brenker, Jonas Maximilian; Gerzen, Arnold (arXiv:2602.04464)
Grocery retailers frequently apply price discounts to stimulate demand for expiring perishables. However, integrating these discounted sales into future demand forecasts presents a significant challenge. This study investigates the effectiveness of incorporating a fixed share of these sales as regular demand into the forecast, as commonly applied in practice. We employ a two-step regression approach on data from a major European grocery retailer, covering over 1,700 products across 676 stores. We reveal that forecasts underestimate actual demand for most SKUs when discounted sales occur. This residual uplift effect is significantly influenced by the number of sales at reduced prices. Our findings underscore the necessity for more precise approaches to integrate discounted sales into demand forecasts, thereby preventing excess inventory and the associated economic and environmental impacts of spoilage in the grocery sector.

An Approach for the Efficient Solution of Eigenvalue-based Inverse Problems for the Material Characterisation Using Guided Acoustic Waves - Zeipert, Henning; Claes, Leander; Hölscher, Jonas; Wippermann, Mareen; Henning, Bernd (Fortschritte der Akustik - DAGA 2026)

Simultaneous measurement of bulk and shear viscosity using guided acoustic waves - Claes, Leander (Fortschritte der Akustik - DAGA 2026)

Der christliche Hilmī Adīb, mein erster Lehrer der Koransure aḍ-Ḍuḥā - Abdelrahem, Mohammed
Keywords: religiöse Koexistenz; Religiöse Bildung; Religionsunterricht

Artificial intelligence in digital service ecosystems—Towards a taxonomy and archetypes - Hansmeier, Philipp; Schäfer, Jannika Marie; zur Heiden, Philipp (Electronic Markets)
Traditional dyadic customer-provider interactions are being shifted to polyadic interactions involving diverse participants in digital service ecosystems. Especially, artificial intelligence (AI) is increasingly integrated into these ecosystems, so that they comprise non-human participants (e.g., AI-based chatbots)—fundamentally altering the nature of value (co-)creation. While existing literature examines human-to-human interactions, knowledge of service interactions between human actors and AI-based systems is still underexplored. To address this research gap, we develop a taxonomy, comprising six iterations, that explores the peculiarities of AI as either a resource or a (non-human) agent in digital service ecosystems. We evaluate our taxonomy using a multiple case study and derive the four archetypes of AI in digital service ecosystems: (1) discriminative experience enhancer, (2) protective ecosystem orchestrator, (3) ecosystem innovation companion, and (4) personalized service composer. Our results extend the knowledge on service science by showing how AI-based systems—discriminative or generative, and focusing on the interaction in the ecosystem or the individual service encounter—assume the role of resources and non-human agents. Researchers and practitioners can utilize our results to augment their ecosystems with AI.

Towards a Service Ecosystem Perspective on Customer Experience: Insights from Hybrid (Online-Offline) Customer Journeys - Hansmeier, Philipp; zur Heiden, Philipp (Behaviour & Information Technology)

Formation of AI Anthropomorphism Structured by the Customer Journey – Towards a Conceptual Framework - Hansmeier, Philipp (Proceedings of the Thirty-Fourth European Conference on Information Systems)

Religion and Health - Comparative-Theological Approaches

Von Lust und Frust im Wissenschaftstransfer - Lebock, Sarah
BloKK-Beitrag für das ZeKK, 09.05.2026

Ultra-Broadband Photonically Assisted Analog-to-Digital-Converters - Witzens, Jeremy; Drayss, Daniel; Fang, Dengyang; Moscoso Mártir, Alvaro; Müller, Juliana; Weizel, Maxim; Zazzi, Andrea; Freude, Wolfgang; Koos, Christian; Randel, Sebastian; Scheytt, J. Christoph (Electronic-Photonic Integrated Systems for Ultrafast Signal Processing)
We present recent progress made towards ultra-broadband photonically assisted analog-to-digital converters, that leverage both the low jitter of best-of-class mode-locked lasers as well as the capability of optics to break down broadband signals into multiple lower speed tributaries that can be better handled by electronics. We review in particular our work on both time- and frequency-domain approaches and give an outlook on how these architectures can be extended to include further signal processing tasks such as equalization. Optically triggered track-and-hold amplifiers are reported with an equivalent jitter below 80 fs rms in a signal frequency range from 20 GHz to 70 GHz. Frequency-domain architectures implementing optical arbitrary waveform measurement up to signal bandwidths of 610 GHz are also shown. Finally, an architecture allowing the deserialization and equalization of PAM4 signals is introduced and modeled for operation in 400 Gb/s links.

Integrated Photonic-Assisted Signal Processing and Thermal Crosstalk - De, Souvaraj; Mandalawi, Younus; Das, Ranjan; Weizel, Maxim (Metrology for THz Communications)
Integrated photonic-assisted signal processing has multiple applications such as signal amplification, multiplexing, and high-Q filtering in optical communication systems, optical sensing systems, and also microwave photonics. We will review recent works on integrated photonic-assisted signal processing for sinc-shaped Nyquist pulse generation, high-bandwidth Nyquist signal detection with low bandwidth devices, arbitrary waveform generation and measurement, and on-chip photonic frequency decoding. However, in such photonic integrated circuits (PICs), the photonic components are placed very close to each other on the chip, resulting in thermal crosstalk which degrades the system performance. Air-filled oxide and deep trench designs have proven to be very effective in mitigating the thermal crosstalk for various frequently deployed photonic devices like Mach-Zehnder modulators (MZMs), ring resonators, optical switches, and photodetectors designed on a standard silicon-on-insulator (SOI) platform. In this chapter, we will additionally review the basics of optical signal processing and some results for such trench-enhanced thermal crosstalk resilient circuits.

Integrated Photonically Assisted Samplers - Weizel, Maxim; Bahmanian, Meysam; Scheytt, J. Christoph (Metrology for THz Communications)
High-speed ADCs operating in the tens of gigahertz up to potentially terahertz range are largely constrained by the jitter in their clock sources. By incorporating photonically assisted samplers that exploit the ultralow jitter of specific mode-locked lasers (MLLs) as analogue ADC frontends, the performance limits of data converters can be pushed to achieve unprecedented levels of accuracy. Continuous advancements in electronic-photonic integration (silicon photonics) are clearing the path for integrating these systems on a chip scale, thereby leading to increased scalability, as well as reduced cost and power consumption.

Simulation and Modelling of Electronic and Photonic Components - Wrana, Dominik; Weizel, Maxim; Haussmann, Simon; Bahmanian, Meysam; Kallfass, Ingmar; Scheytt, J. Christoph (Metrology for THz Communications)
This chapter explores the crucial role of simulation and modelling of electronic and photonic components for terahertz (THz) systems. THz-related challenges already begin with setting up the signal generation and sampling parameters and continue with the realistic modelling of the electronic and photonic building blocks. Hereby, photonic components require not only the modelling of the optical signal propagation but also the modelling of the electronic interface in the THz regime. Furthermore, when advancing to the simulation of systems like fully integrated electronic transmit and receive frontends or photonically assisted analogue-to-digital converters (ADCs), it is up to the designer to find a suitable level of abstraction. Size, complexity, and available computational power versus accuracy must be taken into consideration and prioritized against each other.

Foundations of Information and Knowledge Systems - 14th International Symposium, FoIKS 2026, Hanover, Germany, March 23-26, 2026, Proceedings

Conversion between detector- and rotary-table-related misalignment parameterisations for unified projection-matrix-based geometry calibration in dimensional X-ray computed tomography - Butzhammer, Lorenz (Precision Engineering)

A Numerical Study on the Mutual Influence of Joint Orientation and Component Geometry in Non-Rotationally Symmetric Clinched Joints - Devulapally, Deekshith Reddy; Tröster, Thomas (Materials Science Forum)
Clinched joints with non-rotationally symmetric geometries exhibit orientation-dependent mechanical behavior that is commonly neglected in structural-scale simulations. Reuleaux triangle shaped clinched joints, in particular, show pronounced in-plane anisotropy depending on their orientation. While such effects have been studied at joint and specimen scale, their relevance at the structural level remains largely unexplored. In this work, the influence of joint orientation on the bending response of a joined structure is investigated using numerical simulations. A simplified joint replacement model based on the *CONSTRAINED_SPR2 point-connector formulation in LS-DYNA is employed, with parameters calibrated from previously obtained experimental force displacement data. A hat shaped profile structure subjected to three-point bending is analyzed in a parametric study considering variations in joint orientation, joint spacing, and profile geometry. The results show that joint orientation has little influence during the initial deformation phase but becomes increasingly significant at larger displacements, where joint behavior governs load transfer. Orientation dependent effects are found to influence the global force displacement response and local load redistribution among joints, with magnitudes comparable to those induced by changes in joint spacing and structural geometry. The findings confirm that joint orientation effects remain relevant at the structural level and should be considered in the design of structures assembled using non-rotationally symmetric clinched joints.

Critical Review of Research and Policy on Transitions to School from 2000 to 2024 in Germany - Büker, Petra; Herding, Jana; Henke, Vanessa; Seifert, Anja; Velten, Katrin (Transitions to School in the 21st Century. Insights from National and International Research, Policy, and Practice)